1957
DOI: 10.1017/s0022029900008827
|View full text |Cite
|
Sign up to set email alerts
|

677. The effect of variations in nutrient intake upon the yield and composition of milk: I. Variations in the amount and type of concentrates fed in winter rations

Abstract: 1. A series of five experiments on the effects of variation in the concentrate ration of cows receiving normal diets of hay and grass silage are described.2. Responses in milk yield to the feeding of additional concentrates occurred in all five experiments and were statistically significant in three of them.3. Mean responses in four experiments with adequate statistical control ranged from 0·7 to 1·0 lb. milk/lb. additional S.E. at levels of feeding from 90 to 120% of the Woodman standard, and were not economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1957
1957
1980
1980

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…additional s.E.) upon milk yield (lb./day) was + 0-035 ± 0-04 which is in very close agreement with the value previously reported (23). The predicted response ranged from 0-6 lb.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…additional s.E.) upon milk yield (lb./day) was + 0-035 ± 0-04 which is in very close agreement with the value previously reported (23). The predicted response ranged from 0-6 lb.…”
Section: Discussionsupporting
confidence: 91%
“…The response to a standard amount of additional concentrates was significantly and positively related to milk yield, and there were no independent effects due to stage of lactation. These observations confirm the results of a previous analysis of a series of conventional feeding experiments (23), and the regressions contrast with the results of Jensen et a£. (15) who reported that responses to increased feeding were very similar in 'good' and 'poor' producing cows when the comparison was made at the same percentage of the Haecker production standards for total digestible nutrients.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of the plane of energy nutrition of the cow on the S.N.F. content of milk, as demonstrated in this and earlier work (Burt, 19573;Dijkstra, 1942;Holmes, Reid, MacLusky, Waite & Watson, 1957;Rook, 1953;Rowland, 1946), is represented in Fig. 3.…”
Section: Discussionmentioning
confidence: 52%
“…Concentrate feeding to buffaloes receiving maize silage ad libitum resulted in a significant increase in milk yield which could be explained on the basis of increased intake of D.M. and TDN (Jensen et al 1942;Burt, 1957;Laird & Walker-Love, 1962;Jackson & Gupta, 1971). The SNF content of milk was higher for animals on supplemented rations which is understandable in view of the higher plane of nutrition consequent upon supplementary feeding (Rook, 1961;Huber & Bowman, 1966).…”
Section: Discussionmentioning
confidence: 99%